Anxiety and perception among nurses toward the outbreak of COVID-19 in University of Uyo Teaching Hospital, Akwa Ibom State - Emilia James Oyira; Easter Chukwudi Osuchukwu; Margaret Mombel Opiah; Ndukaku Nwakwe Chinazaekpere; Teresa Achi Osaj; Augusta Nkechi Emeh; Chinedu Godwin Awo (Wolters Kluwer Medknow Publications, 2020)
Purpose: This study sought to examine the anxiety and perception of nurses toward the outbreak of COVID-19 in University of Uyo Teaching Hospital (UUTH). Two research questions one hypothesis were used. What is the level of anxiety among nurses toward the outbreak of COVID-19? What is the perception of nurses toward the outbreak of COVID-19? The hypothesis states that there is no significant relationship between anxiety and perception of nurses toward the outbreak of COVID-19. Literature was reviewed based on the research variables. Methods: The research instrument used in collecting the data for the analysis was a questionnaire administered to 100 nurses in UUTH, Uyo. Their responses were analyzed using frequencies, percentages, and Chi-square analysis, and the following results were obtained. Results: The results indicated that 36 (36%) of the respondents strongly agreed that most nurses perceive that poor provision of equipment's in the hospital result into the transmission of COVID-19 to another person, 35 (35%) agreed, 20 (20%) of the respondents strongly agreed, whereas 9 (9%) of the respondents disagreed. Majority of the respondents 56 (56%) strongly agreed that nurses sometimes perceive that patients sometimes harbor COVID-19 without showing the symptoms. Conclusion: The above data, therefore, showed that nurses in UUTH, Uyo, had moderate perception toward COVID-19.